Positive and Negative Regulatory Mechanisms for Fine-Tuning Cellularity and Functions of Medullary Thymic Epithelial Cells - Akiyama, Taishin; Tateishi, Ryosuke; Akiyama, Nobuko; Yoshinaga, Riko; Kobayashi, Tetsuya J. (Frontiers in Immunology, 2015)
Self-tolerant T cells and regulatory T cells develop in the thymus. A wide variety of cell-cell interactions in the thymus is required for the differentiation, proliferation, and repertoire selection of T cells. Various secreted and cell surface molecules expressed in thymic epithelial cells mediate these processes. Moreover, cytokines expressed by cells of hematopoietic origin regulate the cellularity of thymic epithelial cells (TECs). Tumor necrosis factor (TNF) family RANK ligand, lymphotoxin, and CD40 ligand, expressed in T cells and innate lymphoid cells (ILCs), promote the differentiation and proliferation of medullary TECs (mTECs) that play critical roles in the induction of immune tolerance. A recent study suggests that interleukin-22 (IL-22) produced by ILCs promotes regeneration of TECs after irradiation. Intriguingly, TGF-β and osteoprotegerin limit cellularity of mTECs, thereby attenuating regulatory T cell generation. We will review recent insights into the molecular basis for cell-cell interactions regulating differentiation and proliferation of mTECs and also discuss about a perspective on use of mathematical models for understanding this complicated system.